PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) PADA MATA PELAJARAN GEOGRAFI DI SMAN 1 LANGOWAN - Afriliandy Tumbelaka; Xaverius Erick Lobja; Ellen Eva Poli (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The background of the research is an effort to develop the quality and explore the potential of students. Teachers are strived to use the right learning model, namely problem-based learning models combined with online learning methods (learning from home) that have been decided by the Ministry of Education and Culture during the Covid-19 pandemic. The purpose of this study was to determine the application of problem-based learning models in improving student learning outcomes in geography subjects at SMAN 1 Langowan. The method used is a quasi-experimental design with a pretests-posttests control group design. The research variable with the independent variable is the problem-based learning model and the dependent variable is the learning outcome. The results showed that the problem-based learning model was effective and efficient to improve student learning outcomes. The comparison of learning outcomes shows the experimental class with 76.2 pretests and 87.7 posttests and the control class with 74.4 pretests and 81.8 posttests. It also encourages students to be more active and creative in overcoming the problems encountered in learning.